The influence of knowledge and intellectual capital on the economic outcomes of academic spin-offs: Evidence from Italy - Passavanti Carmine; Simonetta Primario; Rippa Pierluigi (Journal of Innovation & Knowledge, 2025)
This study explores the relationship between intellectual capital and the economic performance of academic spin-offs (ASOs). ASOs are hybrid ventures, distinct from more typical startups and small and medium enterprises because their founders pursue both research and market objectives. Using a sample of 295 Italian ASOs over a 10-year period, the study examines the impact of human, relational, and structural capital, extending the latter to include the adoption of digital technology as a critical factor in business performance. The findings suggest that human capital, especially experience accumulated over time, contributes substantially to improved economic outcomes. Adopting digital technology also emerges as a critical driver of performance, increasing operational efficiency and scalability. Conversely, external equity participation and patent ownership—both traditionally regarded as valuable relational assets—are negatively associated with economic success, suggesting a potential misalignment between the needs of stakeholders and ASOs. These insights highlight the strategic importance of capitalizing on digital technologies and building internal capabilities, while carefully assessing external funding sources and intellectual property strategies. This study contributes to the literature on academic entrepreneurship and intellectual capital by offering new empirical evidence on how intangible assets shape ASOs performance and by challenging conventional assumptions regarding patents and external investors in knowledge-intensive ventures.